2020
DOI: 10.1111/jns.12412
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality rates of Guillain‐Barré syndrome in Serbia

Abstract: Guillain-Barré syndrome (GBS) is an acute auto-immune polyradiculoneuropathy. A huge variety of GBS incidence and mortality rates has been noted across the world. The objective of the present multi-centric study was to assess the incidence and mortality rates of GBS during a 10-year period in Serbia. We collected data of adult GBS patients who were hospitalized from 2009 to 2018 in all five tertiary healthcare centers in Serbia. The incidence rates per 100 000 inhabitants with 95% confidence intervals (CI) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
2
6
0
2
Order By: Relevance
“… 18 , 36 The 1-year mortality rate was 5.0% in the present study, which is similar to previous results in southeast England (8%), Asian countries (6%), Taiwan (4%), and the Netherlands (3.9%), 7 32 35 37 and better than the 6-month mortality rate of 9.7% found in Serbia. 38 Our study also revealed the mortality rate over a very long mean observation period of 9.0 years after the diagnosis. Finally, the SMR of patients with GBS had decreased year by year after the diagnosis, but remained significantly high until 5 years after the diagnosis in the Korean population.…”
Section: Discussionsupporting
confidence: 58%
“… 18 , 36 The 1-year mortality rate was 5.0% in the present study, which is similar to previous results in southeast England (8%), Asian countries (6%), Taiwan (4%), and the Netherlands (3.9%), 7 32 35 37 and better than the 6-month mortality rate of 9.7% found in Serbia. 38 Our study also revealed the mortality rate over a very long mean observation period of 9.0 years after the diagnosis. Finally, the SMR of patients with GBS had decreased year by year after the diagnosis, but remained significantly high until 5 years after the diagnosis in the Korean population.…”
Section: Discussionsupporting
confidence: 58%
“…The most frequent subtype of GBS in both our groups was AIDP. Unrelated to the preceding event, AIDP is the most common subtype of GBS present in about 69–90% of patients [ 22 ] and it is also the most common subtype among GBS patients in our country [ 26 ]. This clinical variant has also been reported as the most frequent subtype of GBS associated with COVID-19 [ 12 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it is an acute bilateral, symmetrical, synchronous, ascending motor and/or sensory impairment. The risk of cardiovascular dysautonomic symptoms and the involvement of chest and bulbar muscles lead to a high mortality of the condition [ 16 ]. The ten deaths recorded in the study were due to APRN alone, resulting in a mortality of 21.3% of APRN cases.…”
Section: Discussionmentioning
confidence: 99%